Studi Kasus Putusan Pengadilan Agama Cianjur Nomor 1808/PDT.G/2018/PA.CJR tentang Pembatalan Perkawinan dikarenakan Pemalsuan Akta Cerai - Elsa Nurjanah; Djanuardi Djanuardi; Sherly Ayuna Putri (Syntax Idea, 2022)
Divorce is the breakdown of the marital relationship between husband and wife. A divorce must have a compelling reason that husband and wife cannot get along again as husband and wife. In Article 65 of the Law on Religious Courts it is asserted that divorce can only be carried out before a Court hearing after the Court concerned has tried and unsuccessfully reconciled the two parties. One of the cases in the Cianjur Religious Court Number 1808/Pdt.G/2018/PA.Cjr where the Plaintiff filed a marriage annulment suit against the marriage of Defendant I and Defendant II who used the fake divorce certificate because Defendant I had never conducted a divorce trial in the Cianjur Religious Court with the Plaintiff. This study aims to determine the validity of marriage annulment because the forgery of divorce certificates and the legal consequences of marriage annulment against.